The pattern of inter-organizational level of connectivity, formal versus informal ties - Lokhman Hakim Osman, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Inter-organizational network exists in many forms. Yet managing them has taken rather a monotonous approach. Using the social network analysis methodology, this study embarks on the objective in elucidating the structure of network depending on the different type of inter-organizational relations. The different pattern of embeddedness in the different type of inter-organizational relationship raise the question of how should we treat the different type of inter-organizational relationships and the pattern of embeddedness. Such questions are important as firms invest heavily in developing and maintaining their network of inter-organizational relationships. , this research will explore what is the structure of the inter-organizational relationships network may look like both in formal and informal network relationship. We seek to determine the different in term of density of connectivity among connected firms as this will indirectly indicate the degree of investment that firm commit to manage the different type of inter-organizational network structure. Findings of this study indicated that firms’ degree of involvement differs in the different type of inter-organizational relationships that they are embedded in. Implication of the findings highlights the importance of network management base on type of inter-organizational relations and selective resource allocations management for inter-organizational network. Future research areas are also discussed.